2008
DOI: 10.1111/j.1472-765x.2008.02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characteristics ofAcacia senegal(L.) Willd. root-nodulating bacteria isolated from soils in the dryland part of Senegal

Abstract: Aims:  We characterized phenotypically and genotypically root‐nodulating bacteria associated with Acacia senegal (L.) Willd. isolated from the soils surrounding A. senegal trees in the dry land area of Senegal. Methods and Results:  The phenotypical and genotypical characterizations we carried out showed a high diversity of A. senegal root‐nodulating bacteria. Phenotypic patterns showed adaptations of the rhizobial strains to many environmental stresses such as heat, drought, and salinity. Twelve molecular gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 42 publications
3
20
1
1
Order By: Relevance
“…Other authors also confirmed the same tolerance characteristics of bacteria with the same growth characteristic (Zerhari et al, 2000;Fall et al, 2008;Rasul et al, 2012), which indicates that the studied mulungu isolates show a potential for inoculation in the semi-arid regions because they are well adapted to the typical stress conditions of these soils.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other authors also confirmed the same tolerance characteristics of bacteria with the same growth characteristic (Zerhari et al, 2000;Fall et al, 2008;Rasul et al, 2012), which indicates that the studied mulungu isolates show a potential for inoculation in the semi-arid regions because they are well adapted to the typical stress conditions of these soils.…”
Section: Discussionsupporting
confidence: 62%
“…Phenotypic characterization is the basis of polyphasic taxonomy and, together with molecular techniques, has contributed to an improved understanding of the physiology and genetic diversity of rhizobia (Zerhari et al, 2000;Fall et al, 2008;Rasul et al, 2012). Among the molecular characterization techniques, fingerprinting by means of Box-PCR generated profiles have been used to examine the diversity of diazotrophic bacteria associated with the (Stocco et al, 2008;Costa et al, 2014;Torres-Júnior et al, 2014) and native species (Fernandes Júnior et al, 2013;Granada et al, 2014) from Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerical genotypic analyses revealed large genetic diversity among root-nodulating bacteria able to nodulate A. senegal (de Lajudie et al, 1998;Fall et al, 2008;Sarr et al, 2005a). However, these studies did not take into account various environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nodules collected in situ (from Goudiry A. senegal plantation in August 2008) and in vitro were surface sterilized, isolated, and authenticated cultures preserved as described by Fall et al (2008). Polymerase chain reactions (PCR) were carried out, on the IGS rDNA of 42 isolates, directly on 2 µl of fresh bacterial culture suspended in 50 µl sterile water, and digested as described by Fall et al (2008).…”
Section: Rhizobial Isolation and Pcr-rflp Of 16s-23s Rdna Intergenic mentioning
confidence: 99%
See 1 more Smart Citation